2020
DOI: 10.1155/2020/1370837
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease-Induced Zebrafish Models: Focussing on Oxidative Stress Implications and Sleep Processes

Abstract: The complex yet not fully understood pathophysiology of Parkinson’s disease includes an important molecular component consisting of oxidative status changes, thus leading to oxidative stress occurrence. While no particular evidence has been reported that describes the relationship between oxidative stress and the molecular mechanisms behind Parkinson’s disease development, animal model studies has shown that oxidative stress induction could modulate Parkinson’s disease symptomatology. Despite the inability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 159 publications
(300 reference statements)
0
29
0
Order By: Relevance
“…Besides, the behaviors and phenotypes demonstrated by zebrafish are relatable to human behaviors. For example, neurotoxin-induced zebrafish exhibits movement impairments such as decreased swimming speed and abnormal swimming behavior, which is equally translated to bradykinesia-like symptoms in PD patients ( Hughes et al, 2020 ; Robea et al, 2020 ). In terms of genetic factors, genome sequencing analysis revealed that the zebrafish genome is 70% similar to the human genome ( Howe et al, 2013 ; Shehwana and Konu, 2019 ), with 80% of the genes located at the same chromosome and in the same order, implying conserved synteny between these two species ( Barbazuk et al, 2000 ; Howe et al, 2013 ).…”
Section: Zebrafish As An Animal Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, the behaviors and phenotypes demonstrated by zebrafish are relatable to human behaviors. For example, neurotoxin-induced zebrafish exhibits movement impairments such as decreased swimming speed and abnormal swimming behavior, which is equally translated to bradykinesia-like symptoms in PD patients ( Hughes et al, 2020 ; Robea et al, 2020 ). In terms of genetic factors, genome sequencing analysis revealed that the zebrafish genome is 70% similar to the human genome ( Howe et al, 2013 ; Shehwana and Konu, 2019 ), with 80% of the genes located at the same chromosome and in the same order, implying conserved synteny between these two species ( Barbazuk et al, 2000 ; Howe et al, 2013 ).…”
Section: Zebrafish As An Animal Modelmentioning
confidence: 99%
“…The discovery of MPTP has opened a new promising opportunity in PD studies because this compound can easily cross the blood brain barrier (BBB) ( Zeng et al, 2018 ). MPTP is metabolized in glial cells by monoamine oxidase B (MAO-B), which causes the conversion of MPTP to its active metabolite, MPP + ( Bajpai et al, 2013 ; Robea et al, 2020 ). Due to its similar structure with dopamine, MPP + is then transported into DA neurons by dopamine transporter protein (DAT) ( Fernagut, 2016 ).…”
Section: Zebrafish As a Model Of Parkinson’s Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…The neuronal circuitries involved in movement in zebrafish are well characterized, with essential molecular mechanisms being highly conserved and analogous to humans. Moreover, despite the remarkable anatomical differences between fish and mammals, it has been shown that more than 70% of all human disease genes have functional homologs in zebrafish [ 17 ]. Zebrafish models of PD have and continue to contribute to our better understanding of familial PD.…”
Section: Introductionmentioning
confidence: 99%